2020
DOI: 10.1186/s12887-020-02287-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of child and family reports of health-related quality of life in pediatric acute lymphoblastic leukemia patients after induction therapy

Abstract: Background: This study aims at determining the health-related quality of life (HRQOL) of children with acute lymphoblastic leukemia (ALL) after the induction therapy, assessing the agreement between child self-reports and family proxy-reports HRQOL, and determining the factors related to this agreement, especially child age, family attendance, and children's social relationships beyond the family. Methods: We analyzed questionnaire data (2012-2017) from the Japanese Pediatric Leukemia/Lymphoma Study Group's cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Although these former studies already highlighted some potential risk factors for altered QoL in childhood ALL patients, differences are encountered between self- and parent-reported QoL [ 12 , 27 ]. More specifically, parents could tend to report more problems in female and in older patients [ 2 , 6 , 16 , 28 ], or more mental symptoms in general than the survivors themselves [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these former studies already highlighted some potential risk factors for altered QoL in childhood ALL patients, differences are encountered between self- and parent-reported QoL [ 12 , 27 ]. More specifically, parents could tend to report more problems in female and in older patients [ 2 , 6 , 16 , 28 ], or more mental symptoms in general than the survivors themselves [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ad hoc follow-up interviews with parents revealed that they misunderstood the question, i.e., by "no problems" they meant "always/often," which is the inverse sense of meaning. However, other studies using PedsQL did not notice such disagreement between children and proxies [ 22 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 88%
“…Thus, there is a strong recommendation that children with cancer should be the primary reporters of their symptoms and if they are unable to provide self-reports caregiver proxy reports should be used [ 12 ]. In addition, an overall lack of fathers as caregiver proxy reporters is noted, and only a limited number of research studies have included both parents but did not separately investigate their perspectives on child’s HRQOL during active cancer therapy [ 12 , 20 , 22 , 23 ]. One recently published study compared 120 paternal and maternal proxy reports concerning agreement on child HRQOL, but the vast majority of children with cancer were post-treatment (mean time since diagnosis 3.3 (± 1.4) years and 87% of the patients had completed therapy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With multi‐agent induction, consolidation, and maintenance chemotherapy, children with ALL enjoy a reasonably good survival. 1 , 2 , 3 , 4 However there are reports of sAML attributable to cytotoxic treatment protocol. 5 , 6 sAML usually occurs with a latency period after the treatment of primary malignancies.…”
Section: Introductionmentioning
confidence: 99%